Educación y comunicación en el Organon de Aristóteles (II) - Pascual, Fernando (Alpha omega, 2001)
The present article intends analyzing some of Aristotle's ideas on communication and education starting from three works contained in the Organon: On Interpretation, Prior Analytics and Posterior Analytics. Aristotle does not limit himself in these works to analyze the fundamental elements of human thought, but rather he makes continuous references to educational topics that show a certain continuity regarding Plato's thought and of his dialogical theory, certainly in a more complete context that allows the elaboration of an interesting theory of communication in the Stagirite.